Therapeutic effects of three-strain probiotic combination on slow transit constipation: mechanistic insights into MAPK signaling pathway and gut microbiota restoration - Liu, Liya; Li, Peiyao; Chen, Youqin; Yang, Guangqing; Cheng, Ying; Liu, Sijia; Zhang, Xinran; Wu, Yulun; Liu, Qihong; Zhao, Peilin; Fang, Wenyi; Ren, Yan; et al. (Frontiers in Pharmacology, 2025)
Three-Strain Probiotic Combination (Golden Bifid), a probiotic formulation composed of Bifidobacterium longum, Lactobacillus bulgaricus, and Streptococcus thermophilus, is widely used to modulate gut microbiota homeostasis and treat various gastrointestinal disorders. However, the specific molecular mechanisms underlying its therapeutic effects in slow transit constipation (STC) remain incompletely understood. In this study, we demonstrated that Golden Bifid alleviates loperamide-induced constipation by coordinately modulating host transcriptomic profiles, particularly the MAPK and serotonin signaling pathways, and restoring gut microbiota composition and diversity. These multi-omics findings provide novel mechanistic insights into the clinical efficacy of this probiotic combination, which have not been previously elucidated. Using a loperamide (LOP)-induced STC rat model, Golden Bifid was shown significantly increase defecation frequency, fecal water content, and intestinal motility, while improving the pathological damage of colonic tissues. It also elevated the protein expression of c-kit, 5-HT, 5-HT3R, and 5-HT4R in colonic tissue. RNA sequencing identified 1,998 differentially expressed transcripts in Golden Bifid group compared with the LOP group, with 899 upregulated and 1,099 downregulated. These transcripts were enriched in pathways, such as the mitogen-activated protein kinase (MAPK), tumor necrosis factor (TNF) and estrogen signaling pathway. Additionally, 16S rDNA sequencing demonstrated that the Golden Bifid partially restored gut microbiota structure, increased microbial diversity, and reversed the dysbiosis induced by LOP, notably reducing the abundance of Patescibacteria and modulating microbial taxa at both the phylum and genus levels to resemble the gut microbiota composition of the control group. These findings suggest that Golden Bifid alleviate STC by enhancing c-kit and 5-HT signaling, modulating the MAPK signaling pathway and pathway and restoring gut microbiota balance, offering promising therapeutic potential for STC treatment.